Evaluation of Thyroid Function During Pregnancy and Its Impact on Perinatal Outcomes - Mishra, Akshara; Chandra, Keerti (Journal of Neonatal Surgery, 2025)
Objectives: The aim of this study was to evaluate the thyroid profile in pregnant women and to compare perinatal outcomes between those with normal thyroid function (euthyroid) and those with thyroid dysfunction. Methodology: This prospective, cross-sectional study included 150 pregnant women. Of these, 75 were healthy women with normal thyroid profiles (Group A), and 75 were pregnant women diagnosed with thyroid disorders (Group B). Results: The most common thyroid disorder identified during pregnancy was subclinical hypothyroidism, accounting for 68% of cases. No significant difference in gestational age at delivery was found between the two groups. However, the rate of cesarean section was significantly higher in Group B (48%) compared to Group A (24%) (p < 0.05). Intrauterine fetal demise (IUD) occurred in 2.67% of cases in Group A and 6.67% of cases in Group B. The mean birth weight of newborns in Group B (2.57 ± 0.50 kg) was significantly lower than that of Group A (2.92 ± 0.60 kg) (p < 0.001). Additionally, a lower APGAR score (≤6) at 1 and 5 minutes was observed more frequently in Group B (30.43% and 18.84%) compared to Group A (8.22% and 4.11%), showing a statistically significant difference (p < 0.01). Conclusion: The findings indicate a significant association between thyroid disorders during pregnancy and adverse perinatal outcomes.